Assessment of the emotional intelligence and its dimensions of medical interns - Singh, Harmesh; Singh, Ishneet; Soni, R. K. (International Journal of Contemporary Pediatrics, 2024)
Background: Emotional intelligence (EI) is multidimensional and includes maturity, sensitivity and competency. It is the skill to identify and understand own and others’ emotions to respond appropriately. Medical interns are expected to have a high degree of EI to face their professional career challenges. During the medical professional training cognitive and clinical skills are evaluated but their EI and its dimensions are nor assessed; hence this study was planned to assess the EI and its dimensions in medical interns. Methods: Objectives were to assess the EI and its dimensions of 140 medical interns. Study design was a descriptive and cross-sectional study. Ethical approval from institutional ethics committee and informed written consent from participants was obtained; administered a questionnaire-based EI test. Data obtained was analysed by ANOVA. Results: Eighty (62.0%) participants were females and 49 (38.0%) males. The mean age of them was 23 years. The mean total EI score was 343.72. It was slightly higher (344.00) in the female interns than in males (343.27). Among the emotional dimensions majority (79.1%) of interns had significantly high (p=0.0001) percentile scores in competency. 67.4% were having significantly lower (p=0.0001) percentile scores in maturity dimension of EI. Sensitivity percentile score was high in 54.3% and low in 45.7% (p=0.7724). Conclusions: This study provides insight about the EI and its dimensions in the medical interns. The maturity and sensitivity are the weaker dimensions of EQ requiring improvement or further development.